Protocols for Endovascular Stroke Treatment Diminish the Weekend Effect Through Improvements in Off-Hours Care - Raymond, Scott B.; Akbik, Feras; Stapleton, Christopher J.; Mehta, Brijesh P.; Chandra, Ronil V.; Gonzalez, Roberto G.; Rabinov, James D.; Schwamm, Lee H.; Patel, Aman B.; Hirsch, Joshua A.; Leslie-Mazwi, Thabele M. (Frontiers in Neurology, 2018)
Introduction: The weekend effect is a well-recognized phenomenon in which patient outcomes worsen for acute strokes presenting outside routine business hours. This is attributed to non-uniform availability of services throughout the week and evenings and, though described for intravenous thrombolysis candidates, is poorly understood for endovascular stroke care. We evaluated the impact of institutional protocols on the weekend effect, and the speed and outcome of endovascular therapy as a function of time of presentation. Method: This study assesses a prospective observational cohort of 129 consecutive patients. Patients were grouped based on the time of presentation during regular work hours (Monday through Friday, 0700hrs-1900hrs) vs. off-hours (overnight 1900hrs-0700hrs and weekends) and assessed for treatment latency and outcome. Results: Treatment latencies did not depend on the time of presentation. The door to imaging interval was comparable during regular and off-hours (median time 21 vs. 19 minutes, respectively, p<0.50). Imaging to groin puncture was comparable (71 vs. 71 minutes, p<1.0), as were angiographic and functional outcomes. Additionally, treatment intervals decreased with increased protocol experience; door-to-puncture interval significantly decreased from the first to the fourth quarters of the study period (115 vs. 94 minutes, respectively, p<0.006), with the effect primarily seen during off-hours with a 28% reduction in median door-to-puncture times. Conclusions: Institutional protocols help diminish the weekend effect in endovascular stroke treatment. This is driven largely by improvement in off-hours performance, with protocol adherence leading to further decreases in treatment intervals over time.